Recent X-ray transients in the M31 disk found with XMM-Newton - Henze, M.; Sasaki, M.; Haberl, F.; Hatzidimitriou, D. (2015)
We report the detection of three new X-ray transients and one recurrent X-ray source in recent XMM-Newton observations of the M31 disk. Two 100-ks observations were carried out on 2015-06-28 (ObsID 0763120101; June) and 2015-08-11 (ObsID 0763120301; August).
Keywords: Nova; Transient